2017
DOI: 10.3847/1538-4357/aa93ea
|View full text |Cite
|
Sign up to set email alerts
|

An X-Ray Study of Two B+B Binaries: AH Cep and CW Cep

Abstract: AH Cep and CW Cep are both early B-type binaries with short orbital periods of 1.8 d and 2.7 d, respectively. All four components are B0.5V types. The binaries are also double-lined spectroscopic and eclipsing. Consequently, solutions for orbital and stellar parameters make the pair of binaries ideal targets for a study of the colliding winds between two B stars. Chandra ACIS-I observations were obtained to determine X-ray luminosities. AH Cep was detected with an unabsorbed X-ray luminosity at a 90% confidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…CW Cep is also characterised as an intrinsically variable polarised object (Elias et al 2008). Both CW Cep and another early B+B binary system AH Cep, were observed with the Chandra X-ray Telescope in search of evidence of a wind-wind collision (Ignace et al 2017). Although CW Cep and AH Cep are comprised of stars with similar properties (cf.…”
Section: Cw Cepheimentioning
confidence: 99%
See 1 more Smart Citation
“…CW Cep is also characterised as an intrinsically variable polarised object (Elias et al 2008). Both CW Cep and another early B+B binary system AH Cep, were observed with the Chandra X-ray Telescope in search of evidence of a wind-wind collision (Ignace et al 2017). Although CW Cep and AH Cep are comprised of stars with similar properties (cf.…”
Section: Cw Cepheimentioning
confidence: 99%
“…Pavlovski et al 2018), X-rays were only detected for AH Cep, even though it is nearly a factor of 2 further away than CW Cep. The authors could not disentangle whether the X-rays detected from AH Cep were caused by colliding winds, or perhaps from magnetic activity originating in one of the other components of the quadruple system of AH Cep (Ignace et al 2017).…”
Section: Cw Cepheimentioning
confidence: 99%
“…2 There is a numerical error in the calculation of the uncertainties in Burkholder et al (1997) as they used an inclination of i = 69.2 o ± 12 o instead of the value of i = 69.21 ± 0.12 given by Bell et al (1986). Ignace et al (2017) analysed Chandra observations and found X-ray variability. They also studied CW Cep, a binary system with very similar physical properties to AH Cep.…”
Section: Ah Cepheimentioning
confidence: 99%
“…Pavlovski et al (2018)), X-rays were only detected for AH Cep, despite it being nearly a factor 2 further away than CW Cep. The authors could not disentangle, however, whether the X-rays detected from AH Cep were caused by colliding winds, or perhaps from magnetic activity originating in one of the other components of the quadruple system of AH Cep (Ignace et al 2017).…”
Section: Cw Cepheimentioning
confidence: 99%
“…CW Cep is also characterised as an intrinsically variable polarized object (Elias et al 2008). Both CW Cep and another early B+B binary system AH Cep, were observed with the Chandra X-ray Telescope in search for evidence of a wind-wind collision (Ignace et al 2017). Although CW Cep and AH Cep are comprised of stars with similar properties (c.f.…”
Section: Cw Cepheimentioning
confidence: 99%